Sistem Informasi Aplikasi Monitoring Revenue Berbasis Web Menggunakan Metode Extreme Programming (Studi Kasus PT. Batu Sarana Persada) - Amellia; Kusyadi , Irfan (CV. Shofanah Media Berkah, 2023)
All kinds of things and and activities can be accesed through the internet, in service, the internet is becoming widely used as media activity for finansial management, primarily because of its contributions to efficiency. This is because internet technology is present asa multipurpose media, and that characteristic makes the internet provide opportunities and benefits in coporate servies, because the internet can stressors the relationship between financial management and company leaders by making it easer to provide interventions to provide financial reporting services because there are many potential benefits to internet use in supporting financial management services, one is managing the financial report in a company’s performance online whitout time and place attached. In deadling with input data management and expenditures of a company, specialized in data management, using the waterfall model, where are current financial management and company leaders wish to create a financial report, to allow for a full accounting of the report within 24 hours and to be accessed anywhere. Therefore, with the application of this company’s financial report website, it is very useful and very helpful for leaders in viewing the results of expenditure data and income data whitout the hassle of seeing the results so that information system canbe accessed easily and can be accessed anywhere, information sytems can provide convenience in viewing the results of monthly financial reports through income ,information systems can provide convenience in financial management performance so that financial reports become more organized.